EFEKTIFITAS PENGGUNAAN STANDAR AKUNTANSI KEUANGAN ENTITAS MIKRO KECIL DAN MENENGAH (SAK EMKM) PADA USAHA MENENGAH - Iis Sulistiyowati; Ayus Ahmad Yusuf; Dendi Purnama (Review of Applied Accounting Research (RAAR), 2021)
This study examines the effect of Education Level, Accounting Understanding, and Business Experience on the Effectiveness of Using Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) in Medium Enterprises in Kuningan Regency. This research was conducted using descriptive and verification methods. The population is all owners and employees of the finance section of medium-sized businesses in Kuningan Regency, totaling 86 respondents. Samples were taken as many as 86 respondents using a Saturated Sample, where the respondent sample was taken entirely. The data collection technique used a questionnaire with data analysis tools in multiple linear regression analysis. The results of this study indicate that the level of education, accounting understanding, and business experience have a simultaneous and significant effect on the effectiveness of using SAK EMKM in medium-sized businesses. Education level has a significant positive effect on the effectiveness of using SAK EMKM in medium-sized businesses. Accounting understanding has a significant positive effect on the effectiveness of using SAK. EMKM in medium-sized businesses and business experience significantly affect the effectiveness of using SAK EMKM in medium-sized businesses.